An Analysis of the Influential Factors on the Social Security feeling in Rural Areas with an Emphasis on Social Capital (Case Study: Marhamat Abad Myani Rural District of Myandoab County) (مسکن و محیط روستا)
Human being chose social life in order to dominate nature, escape insecurity and threat, provide his basic needs and all in all to achieve security and a secure feeling and on the other hand as the society and social contracts grew more and complicated he entered diverse relationships that separated the different aspects of life under rubrics of social, economic, political and cultural which endangered his security altogether. Thus human being has readied a new threat for his own security by forming a society in the first place, a threat that results from the social life itself. Considering the increasing level of social ills and problems in today;#39s societies and communities, an analysis of the sense of social security seems as inevitable as crucial.  Our country’s rural areas, as a host of 30 percent of the whole population, is a place for living so that gaining a knowledge of its people’s sense of security is a necessity in maintaining the population. One of the factors that can play an important role in households’ feeling of security is social capital and its diverse aspects. In the present study, this issue has been considered carefully and scientifically. Therefore, this is an applied research with a descriptive-analytical method. The sample includes the households of the villages in Marhamat Abad Myani rural district of Myandoab county which is located in West Azerbaijan province. According to the 2012 census, this rural area has 1616 households and a population of 7040. The needed sample was 270 according to the Cochran formula. Considering the number of households in every village, a certain number of households were randomly chosen for filling up the questionnaires so that the equal opportunity principle would be observed rightly. A questionnaire of 21 indicators related to the feeling of social security and 28 indicators related to social capital was designed. The level of reliability of the questionnaire was obtained using the Cronbach’s Alpha 0/71 which shows a proper reliability coefficient. The method of analyzing the data was descriptive (mean and standard deviation) and inferential (Kendall test, one-sample t-test, and the Pearson’s correlation coefficient). The study shows that in the indices of social security, having an equal education opportunity for all people and their taking part in elections are the means of the studied households’ sense of social security. The results demonstrate that among the indices related to low environmental pollution, items such as waste disposal, air and water pollution, hygiene and the possibility of entrusting capital to others are not in a very good condition. Also the results show that due to the lethal drought of recent years and Urmia Lake’s worsening situation, the households’ sense of security has been badly damaged and threatened. And in the end, it has been proven that the most effective dimension of social capital on the households’ sense of social security has been the social coherence dimension.